PENGGUNAAN METODE PAIKEM MODEL BROKEN TRIANGLE-SQUARE-HEART UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMA NEGERI 12 PEKANBARU - Putri, Siska Maulana; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is background by the low value of students' repetition on the subjects of class X history SMAN 12 Pekanbaru. This research was conducted in class X IPS 1. Based on these problems, then the formulation of the problem in this study is how to use the method PAIKEM Broken Triangle-Square-Heart model to improve student learning outcomes of grade X SMAN 12 Pekanbaru. The purpose of this research is to know the activity of teachers and students in the implementation of learning process by using PAIKEM model of Broken Triangle-Square-Heart model and to know the influence of Broken Triangle-Square-Heart learning model to student learning result of class X IPS 1 SMAN 12 Pekanbaru on the subject of history. This research was conducted with two cycles by analyzing quantitative data and qualitative data. Quantitative data is obtained from the assessment of learning outcomes through written test of multiple choice and description. While the qualitative data obtained from the observation sheet of student learning activities and teacher teaching activities in the use of PAIKEM model Broken Triangle-Square-Heart. In the first cycle of student learning achievement class X IPS 1 achieve classical mastery of 81.57%. And increased in cycle II by reaching 89.47% classical kentuntasan. Based on the results of this study can be concluded that the use of broken triangle-square-heart model paikem method can improve student learning outcomes of grade X SMAN 12 Pekanbaru on the subjects of history.Keywords: PAIKEM Method, Broken Triangle-Square-Heart Model, Learning Outcome